2017
DOI: 10.1007/s13762-017-1434-8
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of flavonoids and straw mulch application on soil microbial activity in pea rhizosphere

Abstract: The importance of flavonoids in rhizospherelegumes symbiosis has been recognized as critical. However, the limited data are available about their impact on soil microbial communities. In rhizosphere, it remains unclear whether flavonoids, mulch or their joint effects influence on soil microbial diversity and enzymes activity. Therefore, in this study, the effects of flavonoids and straw mulching on soil microbial functional diversity, fungi abundance and enzymes activity (dehydrogenases, protease, acid phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…Our result findings can be explained by the enhanced soil biological activity of the additive decomposer (Zhao et al 2016;Siczek et al 2018) and the optimal soil moisture and temperature condition under FM S tillage (Potthoff et al 2008;Gan et al 2013;Liu et al 2018). Moreover, our results indicated that the fast decomposition period of the buried maize straw lasted for 120 days, with a much lower residual mass rate under T1 than that under T2, which was much longer than the finding in an anaerobic field incubation test of buried wheat straw reported by Wang (2015).…”
Section: Straw Decomposition and Straw C And N Release As Affected Bysupporting
confidence: 57%
“…Our result findings can be explained by the enhanced soil biological activity of the additive decomposer (Zhao et al 2016;Siczek et al 2018) and the optimal soil moisture and temperature condition under FM S tillage (Potthoff et al 2008;Gan et al 2013;Liu et al 2018). Moreover, our results indicated that the fast decomposition period of the buried maize straw lasted for 120 days, with a much lower residual mass rate under T1 than that under T2, which was much longer than the finding in an anaerobic field incubation test of buried wheat straw reported by Wang (2015).…”
Section: Straw Decomposition and Straw C And N Release As Affected Bysupporting
confidence: 57%
“…was (37.88 and 21.21 %), while the increase in DHA-ase activity was (103.57 and 60.71 %) over that obtained under uninoculated plants irrigated by the same saline well. The result substantiates the findings of (Siczek et al, 2017;Cordero et al, 2020 andAbdel Latef et al, 2021). They concluded that under salt stress the total microbial count, nitrogen fixer count and dehydrogenase activity in the canola and pea rhizosphere was enhanced in response to inoculation with growth promoting rhizobacteria.…”
Section: B) Nutrients Content Of Canola Plantssupporting
confidence: 90%
“…Pods of faba bean are rich in phenolic compounds [60], which are important chemicals engaged in diverse processes between plants and microbes: legume-rhizobia and arbuscular mycorrhizal symbioses and plant defense against pathogens [61]. As shown in an earlier study, flavonoids positively effect soil rhizosphere activity [62].…”
Section: Discussionmentioning
confidence: 86%